Influencers on Social Media and Purchase Intention - Sopi Pentana (STIE Amkop Makassar, 2023)
Objective research This method of surveying with the usage of causality is being utilized to learn about the influence of social media influencers. the research sample that was employed This amounts to 371 respondents who are residents of Medan and have ever shopped at MSMEs there. Utilizing a deployment questionnaire to gather data Also, measurements are made using a scale. Method analysis of the data is done using the SMART pls. application software. The study's findings indicate that social media influencers have a major impact on perceived value. Packaging has a tremendous impact on perceived value. Consumer education has a big impact on perceived value. Additionally, taking into account perceived value might buffer the link between social media influencers, product packaging, and consumer understanding and intention to buy.